SYNERGETIC MODELING OF THE SYSTEM OF STATE ORGANIZATION OF SOCIETY. - ZYRIANOV, Aleksey; LIKHOLETOVA, Svetlana; BAUKEN, Alexander (Wisdom, 2022)
The research contained in this work is aimed at actualizing the problem of forecasting the sustainable development of society and the state in the conditions of multifactorial socio-political turbulence observed in the modern world. The stated provisions and conclusions are intended to draw attention to the need to increase the effectiveness of cognitive activity in relation to state-organizational reality through logical and rational tools associated with the development of an appropriate dynamic self-organizational model of the object under study. The article, appealing to the synergetic methodology, expressing the basis of the post-non-classical scientific paradigm, contains an analysis concerning the issues of the ontology of modelling of human-dimensional systems; modelling of crisis states of socio-political systems; program formula of the dynamic model of the state system. The article substantiates the position on the fundamental possibility and importance of carrying out interdisciplinary design and research activities in the state-legal sphere, using methods of mathematical modelling and computer programming, thereby ensuring an increase in the quality of social engineering, predictability and functionality of the system of the state organization of society.